Relationship of vitamin D with the anthropometric indicators and lifestyle of adults. Medellín, Colombia - Nubia Amparo Giraldo Giraldo; Carolina Ramírez Morales; Yelithza Idárraga Idárraga; Ángela Restrepo Moreno; Luz Elena Cano Restrepo; Susana Pamela Mejía de los Ríos (Universidad de Santander, 2023)
Introduction: Serum vitamin D levels depend on sunlight, diet, and other factors. Objective: We aimed to determine serum vitamin D levels and evaluate their relationship with anthropometric indicators and lifestyle habits in apparently healthy volunteers. Materials and Methods: In this cross-sectional study (n=75), socio-demographic, anthropometric, and lifestyle habit-related data were collected. Serum vitamin D levels were determined with high performance liquid chromatography, food intake was measured by semiquantitative frequency and nutritional status was assessed by anthropometry. Chi-square test and also principal component analysis were used to analyze the relationship between some variables and vitamin D status. Spearman's test was used to determine correlations between quantitative variables. Results: 73% were women and 61% belonged to medium socio-economic level. Median vitamin D intake was 137 (83.1-227.3) IU/day. Based on body mass index (BMI), 44% individuals had overweight/obesity. The 68% exhibited deficient/insufficient vitamin D levels (Hypovitaminosis D). BMI classification and waist circumference (CW) were not related with vitamin D status; however, activities with higher sun exposure were highly related (p = 0.013). Sun exposure time explained variation in component 2 (16.60%), where most of the individuals with normal level were grouped. Sun exposure time was positively correlated with vitamin D status (r = 0.263; p = 0.023). Discussion: Excess weight and abdominal obesity are not always associated with hypovitaminosis D. Conclusions: The majority of individuals showed hypovitaminosis D but their status was not related with anthropometric indicators. A Sun exposure time was the only factor positively correlated with vitamin D status.